Hybrid lattice Boltzmann 3D simulation of combined heat transfer by conduction, convection and radiation - Alexander Nee; Ali J. Chamkha (Case Studies in Thermal Engineering, 2022)
In this study, the hybrid lattice Boltzmann scheme is introduced for three-dimensional heat transfer by conduction, natural convection and radiation. The mesoscopic LBGK model with the D3Q19 stencil is used to describe the flow pattern whereas the thermal model is formulated in terms of the finite difference solution of the macroscopic energy equation. The governing equations are solved in MatLab by means of the in-house code validated on experimental and numerical benchmark data. Three-dimensional heat transfer and flow patterns are analyzed when varying the Rayleigh number 104≤Ra≤106, solid-fluid interfaces emissivity 0≤ε≤1, walls thickness 0.05≤M≤0.2. During numerical simulations, it is found that temperature of the air and solid walls is reduced with an increment in the Rayleigh number under studied conditions. However, the flow field is slightly altered with Ra. Computational performance of the hybrid lattice Boltzmann model is significantly better than the conventional vorticity-vector potential formulation. No radiation heat transfer mode provides thermal stratification in the entire cavity. Along with that, thermal and flow behavior are very similar under the 2D and 3D simulations. On the contrary, a significant discrepancy is observed in the temperature and velocity values when taking into account surface radiation. Hence, it is very important to implement the 3D model when studying conductive-convective-radiative heat transfer under the top location of the heater.